2017
DOI: 10.3329/kyamcj.v7i2.33832
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postdural Puncture Headache after Caesarean Section Comparison Between 25G and 27G Quincke Variety of Spinal Needle

Abstract: Background: Post dural puncture headache is related to the size as well as type of the spinal needle used 90 . It is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…21 Rahman et al (2017) 6.7% frequency of PDPH with with 27G Quincke needle and 16.7% with 25G Quincke needle. 22 In our study, at the completion of the study, patients that had received spinal anaesthesia with 25 G needle (28%) had high PDPH in comparison with other group who received it with 27G needle (8%) and had statistical significance. There are some other studies which have compared the frequency of PDHD by using two different sizes of the needles.…”
Section: Discussionmentioning
confidence: 53%
“…21 Rahman et al (2017) 6.7% frequency of PDPH with with 27G Quincke needle and 16.7% with 25G Quincke needle. 22 In our study, at the completion of the study, patients that had received spinal anaesthesia with 25 G needle (28%) had high PDPH in comparison with other group who received it with 27G needle (8%) and had statistical significance. There are some other studies which have compared the frequency of PDHD by using two different sizes of the needles.…”
Section: Discussionmentioning
confidence: 53%
“…They found incidence of headache 16.7% in 25 guage patients and 6.7% in 27 guage patients. 19 Another study conducted by Anirudh and colleagues reported 26% incidence of PDPH using 25-G Quincke needle as compared to 27-G needle in full term parturients admitted for elective caesarean section. 20 Anisul Islam documented 12% incidence of post dural puncture headache in 25-G Quincke group and 2% in the 29-G Quincke group while incidence of failure of spinal anaesthesia was more with 27-G needle as compared to 25 guage i.e.…”
Section: Discussionmentioning
confidence: 99%